2023
DOI: 10.3390/molecules28062485
|View full text |Cite
|
Sign up to set email alerts
|

Allii Macrostemonis Bulbus: A Comprehensive Review of Ethnopharmacology, Phytochemistry and Pharmacology

Abstract: The dried bulbs of Allii Macrostemonis Bulbus (AMB) are called “薤白” in China and are mainly distributed in Asia. The plant species included in the 2020 Edition of the Chinese Pharmacopoeia (ChP) are Allium macrostemon Bunge (called xiaogensuan in Chinese, A. macrostemon) and Allium chinense G. Don (called xie in Chinese, A. chinense), respectively. In the traditional Chinese medicine (TCM) theoretical system, AMB is warm in nature, acrid-bitter taste, and attributive to the heart, lung, stomach, large intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…The chemical components of Allii Macrostemonis Bulbus are typically classified as volatile oils, nitrogenous compounds, steroidal saponins, and other constituents. SAMB exhibits remarkable biological properties among these compounds and holds great potential for treating atherosclerosis 35 . Along this line, in the present study, we first reported that oral administration of SAMB significantly ameliorated HFD-induced atherosclerosis in ApoE −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical components of Allii Macrostemonis Bulbus are typically classified as volatile oils, nitrogenous compounds, steroidal saponins, and other constituents. SAMB exhibits remarkable biological properties among these compounds and holds great potential for treating atherosclerosis 35 . Along this line, in the present study, we first reported that oral administration of SAMB significantly ameliorated HFD-induced atherosclerosis in ApoE −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…There is still a lack of investigations on AMBs’ regulation of endothelial function. The current study aimed to understand how SAMB (saponins from AMBs), the main active component of AMBs [ 34 ], protect ECs by inhibiting inflammation in vitro and in vivo. In vitro, we utilized both the exogenous inflammatory mediator lipopolysaccharide (LPS) and the endogenous inflammatory mediator tumor necrosis factor-α (TNF-a) to investigate the impact of SAMB on inflammation in human umbilical vein ECs (HUVECs).…”
Section: Introductionmentioning
confidence: 99%
“…The whole plant of AMB is edible, with a unique flavor and pungent taste, which not only improves appetite, but also has an antiseptic effect, and is one of the common dishes on the table; its bulb can be used as medicine for treating coronary heart disease, epigastric and abdominal distension, and diarrhea. Remarkably, AMB has earned official recognition as both a homology of medicine and food, as stipulated by the National Health and Wellness Commission of the People's Republic of China, attesting to its elevated status in terms of both edibility and medicinal efficacy ( Wu et al, 2023b ). Previous investigations have revealed a diverse array of bioactive constituents within AMB.…”
Section: Introductionmentioning
confidence: 99%